Perancangan Kampanye Berkebaya untuk Melestarikan Budaya Indonesia kepada Gen Z - Vanesha, Vanesha; Susanti, Elizabeth; Yonatia, Jessica (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Many Indonesian women no longer wear kebayas because they consider them impractical and prefer modern clothing. This research aimed to create a campaign by creating visual communication design media so that Indonesian women want to wear kebayas in their daily lives. The method used in the research is descriptive, with data obtained from interviews, questionnaires, which were responded to by 112 respondents, and literature studies. The research results used above, below, and through-the-line media techniques. The media used were posters, billboards, Instagram, and creating a booth by distributing brochures, tote bags, and notebooks. This campaign will make Indonesian women aware of their love of Indonesian culture and want to wear kebaya daily.